Pendampingan Pembuatan Batik Ikat Siswa MTs. Sunan Drajat Banjarwati Paciran Lamongan - Siti Aminah; Alfi Zakiyatul Fakhiroh; Amirotul Azmi; Nur Indah Elviana; Alivia Dewi Intan; Kartika Novi Astuti; Nor Afiyah (KERIS : Journal of Community Engagement, 2021)
In the era of the industrial revolution, the level of development of science, technology and information as well as the arts brought mutual benefits to the development of traditional batik in Indonesia Batik as one of the characteristics of the Indonesian state is currently increasingly in demand by various groups as well as among the types of batik, namely batik jumputan which is batik by means of dyeing it. Which will be studied in extracurricular works. The purpose of holding assistance in making batik ikat for MTS Sunan Drajat students is as an effort to support the development of student creativity in producing a product. The method for implementing this mentoring activity is the author uses an ABC Asset Based Community Development approach. These activities include initial communication, identification of dreams, designing steps to determine goals and steps implementation. This refers to the steps of the ABCD approach, the discovery of dreams, the definition of design, and destiny. The results of the research show that asset identification encourages community members to realize the power of assets. With the addition of this assistance, they will immediately realize their dreams by making plans and designing procedures to achieve them. Set goals and start building their community ready to become facilitators and motivators of peers. This mentoring can be a sustainable development activity and involve more community members.